STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM UPAYA MEWUJUDKAN SEKOLAH EFEKTIF - Istikomah, Istikomah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
An effective school is a school which is able to achieve its desired goal (s) or to produce its desired output (s). Studies showed that an effective school has certain characteristics which are a) the determination to achieve better results, b) maximization of actual net learning time, and c) structured teaching. Consequently, an effective school requires principal leadership to direct, motivate and give support to all school members: teachers, staff, students, school’s communities, and stakeholders to do what should do at their best for a better result (s) or output (s). To be effective, principal leadership strategies should consider the contexts where leadership takes place. There are four possible leadership strategies. They are bartering, building, binding, and bonding. Each strategy is considered more suitable than others in a particular context.